STRATEGI PEMASARAN SUWAR SUWIR DENGAN METODE SWOT DAN AHP (STUDI KASUS PADA INDUSTRI MIKRO UD. SUWAR SUWIR DOHO KABUPATEN JEMBER) - Rizky Chandra Ardi Wardhana; Mahardika, Nidya Shara; Kuswardhani, Nita (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Jember, 2022)
The rapid development of the business world demands that every business must always make gradual and continuous improvements in order to be able to compete in this digitalization era, including MSMEs (Micro, Small and Medium Enterprises) in Jember Regency. This resulted in increasingly limited market opportunities, one of the MSMEs that felt the impact, namely the DOHO suwar suwir, a SWOT (Strength, Weakness, Opportunities, Threats) and AHP (Analytical Hierarchy Process) analysis was carried out which would be linked to the AHP method. The combination of SWOT analysis with the Analytic Hierarchy Process (AHP) approach aims to produce an analysis that is able to prioritize marketing strategies based on the most important criteria. The results obtained from the DOHO suwar suwir SWOT analysis are diversification strategies, based on the results of AHP calculations having the highest partial value with the first priority on, namely by developing product marketing potential by updating marketing methods, the second priority is prioritizing product quality by looking at purchasing power and consumer demand, the third priority is to prioritize consumer loyalty.